Commercial Corridor Development Strategy Through the Application of the Walkable Commercial Strip Concept in Urban Area of Jember City - Sulistyono, Sonya; Koesoemawati, Dewi Junita; Hayati, Nunung Nuring; Angelina, Callista (Universitas Diponegoro, Indonesia, 2024)
Walkability is an essential concept to consider when planning a sustainable city. This study aims to determine the walkability development strategy of the Jember City commercial corridors urban area based on people's and experts' perceptions of the Walkable Commercial Strip concept. The study was conducted in the urban area of Jember City Golden Triangle. The methods of analysis used in this study are ordinal logistic regression and AHP. Based on people's perceptions, the concepts that have the highest odds of influencing the first corridor's walkability level are the ones related to the available amenities variable, while the concept that has the highest odds of influencing the second and the third corridors' walkability level is the concept that is related to the walking path modal conflict variable. The order in which corridors have the highest development priority starts with the first corridor, Gajah Mada - Sultan Agung Street, followed by the second corridor, Ahmad Yani Street, and ends with the third corridor, Trunojoyo Street – HOS Cokroaminoto Street. The walkability development strategy for the urban area of Jember City commercial corridors is to start the order of development according to the order of priority and apply the development concepts that have the highest opportunity to influence the walkability level of each corridor based on people's perception.